Le Paléolithique supérieur de l'abri Pataud (Dordogne) Les fouilles de H. L. Movius Jr. - Bricker, Harvey M. (Documents d'archéologie française, 1995)
One of the large international and interdisciplinary research projects on the Palaeolithic of France during the middle of the 20th century was the excavation of the abri Pataud (Les Eyzies, Dordogne). From this project, directed by Hallam L. Movius, Jr., came innovations in excavation technique and artifact analysis that have contributed to the methodological synthesis underlying current research. The abri Pataud is one of the key sequences of the earlier Upper Palaeolithic in the Southwest. The publication began in 1975 but was left unfinished because of the death of Pr Movius in 1987. His closest collaborators have summarized here the results of the project, including unpublished studies of the Protomagdalenian, Middle Perigordian, and Aurignacian occupations, new radiocarbon dates, a reappraisal of the geochronology, and an extensively annotated catalogue of Aurignacian and Perigordian sites in Dordogne which allows the abri Pataud to be seen in its regional context.